1983
DOI: 10.3382/ps.0620465
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Metabolism in Broiler Breeder Hens

Abstract: Experiments were conducted to determine the influence of time of dietary calcium intake on eggshell quality in broiler breeder hens. In Experiment 1, 60 hens were randomly divided among three treatment groups. The control group received 155 g feed (3.1% calcium) per day at 0800 hr whereas the morning- (a.m.) and evening-fed (p.m.) treatments received a .42% calcium diet (155 g/bird) and were intubated with 4.2 g calcium at 0800 or 1600 hr, respectively. Egg weight, shell weight, and specific gravity were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

1983
1983
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 10 publications
0
10
2
Order By: Relevance
“…As the concentrate (placed upon the grains) is transported along the circuit, it successively falls through and mixes with the grain, concentrate thus being consumed first by the birds at the start of the run and later by birds at positions further on along the circuit. Several authors have reported inferior egg shell quality in hens receiving the calcium early in the day before egg shell calcification occurs, compared to calcium offered late in the day closer to the calcification phase (Mongin & Saveur, 1979;Hellwig et al, 1982;Farmer et al, 1983;Roland, 1984). Although the trends in SCF-B would not be a serious problem in longer circuits, they raise the question of the optimum time for delivery of concentrate.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As the concentrate (placed upon the grains) is transported along the circuit, it successively falls through and mixes with the grain, concentrate thus being consumed first by the birds at the start of the run and later by birds at positions further on along the circuit. Several authors have reported inferior egg shell quality in hens receiving the calcium early in the day before egg shell calcification occurs, compared to calcium offered late in the day closer to the calcification phase (Mongin & Saveur, 1979;Hellwig et al, 1982;Farmer et al, 1983;Roland, 1984). Although the trends in SCF-B would not be a serious problem in longer circuits, they raise the question of the optimum time for delivery of concentrate.…”
Section: Discussionmentioning
confidence: 96%
“…(Petersen, 1972(Petersen, , 1977Blair et al, 1973;Emmans, 1975Emmans, . 1977Emmans, and 1982Dun et al, 1978;Heam et al, 1979;Leeson & Summers, 1979;Herstad, 1980;Summers & Leeson, 1981;Farmer et al, 1983;Elwinger & Nilsson, 1984;Saveur & Clavreul, 1984;Robinson, 1985). Production results compared to all mash meal feeding have varied according to models used.…”
Section: Introductionmentioning
confidence: 94%
“…It normally begins in the afternoon or evening, and the utilization of dietary Ca in morning-fed broiler breeders is poor due to the inability of these hens to maintain Ca from the crop to the lower digestive tract at a uniform rate (Farmer et al, 1983a). Feeding broiler breeders later in the day supplies dietary Ca at times that correspond more closely to periods of shell deposition (Farmer et al, 1983a), resulting in a better Ca utilization (Farmer et al 1983b;Roland and Farmer, 1984), which is usually manifested as an increase in egg specific gravity, eggshell weight and shell thickness (Backhouse and Gous, 2006). In this study, the highest egg specific gravity was observed in hens fed at 3:00 PM (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of hens to produce good quality shell depends largely on the availability of calcium (Ca) from the ingested food and skeletal reserves (Farmer et al, 1983). Washburn (1982) corroborated that Ca is the most important dietary factor affecting shell quality.…”
Section: Feed Intake and Eggshell Quality In Hot Environmentsmentioning
confidence: 93%